Abdominal wall defects: pathogenesis, prevention and repair. Issue 2 (February 2021) - Mackenzie, Paul; Maclean, William; Rockall, Timothy
Abstract: 'Abdominal wall defects' is a collective term used to describe two distinct pathologies: primary ventral hernias and incisional hernias. This article describes the pathogenesis, risk factors and the management of each.